RESPONS TANAMAN TERONG UNGU TERHADAP KOMBINASI PEMBERIAN PUPUK ORGANIC CAIR LIMBAH SAYURAN DAN PUPUK NPK - Miftahurridho, A Muhammad Toha; Irianto, Irianto; Rinaldi, Rinaldi (Jambi University, Fakultas Pertanian, Program Studi Agroekoteknologi, 2025)
ABSTRACT Eggplant (Solanum melongena L.) is a vegetable that is loved by the community because it tastes good and has health benefits. Eggplant productivity in Jambi province has not yet reached its potential results, this is because the land used for planting has low fertility. Efforts to increase productivity are carried out by fertilization. Fertilizers are divided into two, namely organic and inorganic fertilizers, each of which has advantages and disadvantages so it needs to be combined to get efficiency. Organic fertilizer used in the form of liquid organic fertilizer (POC) from vegetable waste. This research aims to find out the response of purple eggplant plants to the administration of liquid organic fertilizers, vegetable waste and NPK fertilizers. The research was carried out at the Teaching and Research Farm of the Faculty of the Faculty of Agriculture, University of Jambi, which used a random group design (RAK) with a combination treatment of liquid organic fertilizer for vegetable waste and NPK fertilizer with 5 levels, namely: 0 mL POC vegetable waste + 30 grams of NPK; 50 mL POC vegetable waste + 22.5 grams of NPK; 100 mL POC vegetable waste + 15 grams of NPK150 mL POC vegetable waste + 7.5 grams of NPK; 200 mL POC vegetable waste + No NPK Fertilizer. The results of the study showed that the combination of liquid organic fertilizer from vegetable waste and NPK fertilizer had an effect on the growth and yield of purple eggplant plants including plant height, number of leaves, number of branches, flowering age, crown diameter, number of fruits per plant, fruit weight per plant, average fruit weight per plant, average fruit length, and average fruit diameter. The combination of 100 mL POC of vegetable waste and 15 grams of NPK fertilizer gives the highest number of leaves, fruit length and fruit diameter. Keywords: NPK, POC, eggplant.